Pragmatic Analysis of Illocutionary Act Used in Quarrelling Scene of “Ted 2” Movie - Bramantio, Faza Ghalib Miko; Gunawan, Hero (JALL (Journal of Applied Linguistics and Literacy), 2025)
This research examines the use of illocutionary speech acts in the quarrelling scenes of the film "Ted 2," employing a pragmatic approach to analyze how characters communicate emotions and intentions during conflicts. Understanding speech acts in cinematic dialogue is crucial for comprehending character dynamics and narrative development. The research aims to identify the types and functions of illocutionary acts present in the film's argumentative exchanges. Using a qualitative descriptive methodology, the study analyzes transcripts of selected quarrelling scenes, focusing on verbal interactions and contextual cues. Data analysis follows Searle's classification of illocutionary acts: assertive, directive, expressive, commissive, and declarative. Findings reveal a predominance of assertive and expressive speech acts in the analyzed scenes, reflecting characters' tendencies to state facts and express emotions during conflicts. Directive acts are also significant, indicating attempts to influence others' behavior. The study concludes that the distribution and functions of illocutionary acts in "Ted 2" contribute to the portrayal of character relationships and conflict escalation. This analysis enhances our understanding of how language functions in conveying relational conflicts within cinematic narratives, offering insights into the pragmatic aspects of film dialogue.